Tecsun : a utopia ruled with care and love - Xu, Jingyue; Jiao, Shubin; Zhao, Lei, active 2018 (London : Renmin University, 2018)
This case explores the grounds and prospects of the utopian managerial approach of Tecsun (Suzhou) Homes that features paternalistic leadership. It explains the founder's management philosophy with "education" and "enlightenment" as the core, and it demonstrates his leadership style of "paternalistic" in China and "godfather" in the West from multiple perspectives. It further analyzes the influence of the founder's leadership style on employee activation and on the growth mode of the company, offering students insights into the challenges faced by the company and prompts them to think about the issue of sustainability.
Originally Published InXu, J., Jiao, S. & Zhao, L. (2018). TECSUN: A Utopia Ruled with Care and Love. Beijing, China: Renmin University Business School.
Includes bibliographical references.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Tecsun (Firm) -- Case studies; Personnel management -- China -- Case studies; Leadership -- China -- Case studies